A type of I-based - / I5 - Reversible electrochromic devices, their fabrication methods and applications

CN123010293APending Publication Date: 2026-10-30HAINAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611069521.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,传统碘基体系存在显著的穿梭效应,生成的I2易与I-反应,形成 I3-、I5-等可溶性多碘化物,这些多碘化物会在电解质中扩散,并引发严重的穿梭效应

Benefits of technology

1.本发明的四甲基碘化铵具有高对称四面体结构的四甲基铵阳离子N1111+,作为I5-的特异性配位单元,因其有序堆积模式能够和I5-分子精准匹配,构建出高晶格能、稳定的固态N1111I5复合物,抑制I5-的穿梭。具体的:本发明的水系电解液中引入N1111+不仅在电极/电解质界面迅速捕获生成的I5-并与之共沉积,形成黑色、高光学密度的固态N1111I5膜,能够实现高效着色,并在还原电压下可逆褪色至无色态,实现了稳定且可逆的从无色到黑棕色的电致变色调制,有利于抑制穿梭和自放电。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123010293A_ABST
    Figure CN123010293A_ABST
Patent Text Reader

Abstract

This invention provides a method based on I ‑ / I5 ‑ This invention relates to the field of electrochromic devices technology, specifically a reversible electrochromic device, its fabrication method, and its applications. The electrochromic device fabricated in this invention exhibits Icoloration during coloring. ‑ I5 is generated by oxidation on the working electrode side. ‑ It forms a black solid N with tetramethylammonium cations. 1111 When the I5 film fades, the solid film reverts to I. ‑ And then re-enter the electrolyte. Tetramethylammonium cations against I5 ‑ Solid-state complexation can inhibit polyiodide shuttle, and the RuO2 catalyst layer can reduce I ‑ / I5 ‑ Conversion energy barrier. Verification through examples showed that the coloring / fading response time of the device in the examples was 3.9s and 6.5s, and the coloring efficiency was 49.8 cm⁻¹. 2 •C ‑1 It also boasts an ultra-long cycle life; after 20,000 uninterrupted coloring / fading cycles, its optical modulation still retains 84.9% of its initial value. The electrochromic device of this invention has a simple structure, fast response, and stable cycling performance, making it suitable for tunable devices and showing promising application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochromic device technology, and particularly to a device based on I - / I5 - Reversible electrochromic devices, their fabrication methods, and applications. Background Technology

[0002] Building energy consumption is one of the major sources of global energy consumption and carbon emissions, accounting for approximately 30%-40% of total global energy consumption and contributing about 27% of carbon dioxide emissions. Electrochromic smart windows, which can actively and on-demand control light and heat transfer through applied voltage, are considered an important technological approach to achieving building energy conservation and carbon reduction. The electrochromic layer is the core functional layer of the electrochromic smart window, and its performance directly determines the optical modulation amplitude and cycling stability of the device. Traditional electrochromic layers are typically prepared by pre-depositing electrochromic materials, such as WO3, V2O5, and Prussian blue PB electrochromic films, on a transparent conductive substrate. However, during electrochemical cycling, the repeated insertion and extraction of ions easily leads to degradation of the material's crystal structure, causing performance degradation and shortened lifespan, and increasing the complexity of large-area film preparation, thus limiting its feasibility in large-area device applications.

[0003] To address the aforementioned issues, existing technologies have proposed electrochromic smart window systems based on metal electrodeposition (Bi, Cu, Zn, etc.). These systems eliminate the need for pre-fabricated electrochromic films, relying instead on the redox reaction of metal ions in the electrolyte to achieve electrochromic functionality, significantly simplifying the device fabrication process. However, this strategy still faces two challenges: 1. Reliance on precious metals such as silver and bismuth leads to high costs; 2. Inhomogeneous nucleation and growth of metals during electrodeposition can easily induce dendrite formation, resulting in uneven coloring. Furthermore, dendrites dissolve into insoluble metal fragments that deposit in the electrolyte, severely limiting the optical modulation range and cycling stability of the electrochromic smart window.

[0004] In contrast, the electrochromic mechanism based on nonmetallic redox reactions offers a novel approach to constructing highly stable systems. Halogen systems, especially iodine systems, can exhibit electrochromic properties in colorless I-containing compounds. - It undergoes reversible transformation with colored I₂ / polyiodides, exhibiting intrinsic electrochromic properties. Furthermore, the low conductivity of iodine itself helps alleviate localized current concentration, thereby inhibiting dendrite growth to some extent. However, traditional iodine-based systems exhibit a significant shuttle effect, and the generated I₂ readily reacts with I₂... - The reaction forms I3. - I5 -Soluble polyiodides diffuse in electrolytes, causing severe shuttle effects. This dissolution-diffusion process disrupts the spatial locality of redox reactions, leading to self-discharge, reduced optical contrast, and poorer cycle stability, becoming a major bottleneck limiting their practical applications. As the most thermodynamically stable and dominant oxidation state species in iodine-based systems, the solid-state transformation behavior and interfacial stability of polyiodides currently lack effective control strategies.

[0005] Therefore, it is necessary to construct a spatially confined solid-state multiiodide deposition pathway and achieve highly reversible Ig deposition. - Polyiodide conversion is key to the development of durable non-metallic electrochromic systems. Summary of the Invention

[0006] In view of this, the present invention proposes a method based on I - / I5 - This invention provides a reversible electrochromic device, its fabrication method, and its applications, addressing the aforementioned problems. The technical solution of this invention is achieved as follows: A type of I-based - / I5 - The fabrication method of reversible electrochromic devices includes the following specific steps: S1. Preparation of aqueous electrolyte Tetramethylammonium iodide, ZnCl2 and ZnI2 were added to water and stirred until homogeneous to obtain an aqueous electrolyte. S2. Assembly of electrochromic devices Using RuO2 / transparent conductive substrate as the working electrode and zinc-containing electrode as the counter electrode, the aqueous electrolyte is sandwiched between the working electrode and the counter electrode and sealed to obtain an electrochromic device.

[0007] Furthermore, in step S1, the molar concentration of tetramethylammonium iodide in the aqueous electrolyte is 0.8-1.2 mol / kg, the molar concentration of ZnCl2 is 9-11 mol / kg, and the molar concentration of ZnI2 is 0.4-0.6 mol / kg.

[0008] Furthermore, in step S2, the RuO2 / transparent conductive substrate electrode is prepared by depositing a RuO2 thin film on a transparent conductive substrate using DC reactive magnetron sputtering, with the sputtering atmosphere being a mixture of Ar and O2.

[0009] Furthermore, the transparent conductive substrate is FTO conductive glass or ITO conductive glass.

[0010] Furthermore, the specific method for preparing the RuO2 / transparent conductive substrate electrode is as follows: the transparent conductive substrate is ultrasonically cleaned sequentially with anhydrous ethanol and deionized water for 10-20 min; the cleaned transparent conductive substrate is then subjected to ultraviolet ozone treatment for 10-15 min; the ultraviolet ozone-treated transparent conductive substrate is mounted on a rotating support; and ruthenium metal target is used for DC reactive magnetron sputtering. The sputtering conditions are: sputtering atmosphere Ar flow rate 10-12 sccm, sputtering atmosphere O2 flow rate 7-8 sccm, sputtering pressure 3-4 Pa, sputtering power 40-45 W, deposition time 5-15 min, and the distance between the ruthenium metal target and the transparent conductive substrate is 10-12 cm.

[0011] Furthermore, in step S2, the counter electrode is any one of a zinc foil frame, a zinc grid, or a zinc sheet attached to the surface of the glass substrate.

[0012] Furthermore, in step S2, a spacer with a thickness of 0.5-2.0 mm is provided between the working electrode and the counter electrode, and it is sealed with UV-curable adhesive.

[0013] A type of I-based - / I5 - The reversible electrochromic device is prepared by any of the above-described methods.

[0014] Furthermore, the electrochromic device includes a working electrode, a counter electrode, and an aqueous electrolyte; At a coloring voltage of 1.2-1.6V, I - I5 is formed by oxidation on the working electrode side. - I5 - The tetramethylammonium cation in the aqueous electrolyte forms a solid tetramethylammonium pentaiodide, which is deposited on the surface of the working electrode, coloring the device. Under a bleaching voltage of 0.7-0.9V, the solid tetramethylammonium pentaiodide is reduced to I... - It dissolves and causes the device to fade.

[0015] A type of I-based - / I5 - Applications of reversible electrochromic devices in the fabrication of energy-efficient building windows, automotive dimming windows, or privacy dimming devices.

[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. The tetramethylammonium iodide of the present invention has a highly symmetrical tetrahedral structure and a tetramethylammonium cation N 1111 + As I5 - The specific coordination units, due to their ordered stacking mode, can interact with I5 - Precise molecular matching enables the construction of a high-lattice-energy, stable solid-state N2.1111 I5 complex, inhibiting I5 - The shuttle. Specifically: N is introduced into the aqueous electrolyte of this invention. 1111 + Not only does it rapidly capture the generated I5 at the electrode / electrolyte interface - It co-deposited with it to form a black, high optical density solid N. 1111 The I5 film enables efficient coloring and reversible fading to a colorless state under reduction voltage, achieving stable and reversible electrochromic color modulation from colorless to dark brown, which is beneficial for suppressing shuttle and self-discharge.

[0017] 2. The RuO2 catalyst layer of the present invention can reduce I - / I5 - Redox reaction energy barrier for I - / I5 - The conversion has a significant catalytic effect, which can reduce the reaction overpotential and coloring voltage, while having little impact on the original transmittance of the transparent conductive substrate.

[0018] 3. The electrochromic device prepared by this invention, as verified by examples, achieves an optical modulation amplitude of up to 75.5% at 650 nm, exhibiting excellent electrochromic performance; furthermore, it possesses fast ion transport kinetics, with coloring / fading response times of 3.9 s / 6.5 s and a high coloring efficiency of 49.8 cm⁻¹. 2 •C -1 It also features an ultra-long cycle life; after 20,000 uninterrupted coloring / fading cycles, its optical modulation amplitude still retains 84.9% of its initial value. The electrochromic device of this invention has high optical contrast, short response time, excellent durability, and the highest coloring efficiency.

[0019] 4. The electrochromic device of the present invention consists of a transparent conductive working electrode, an aqueous electrolyte, and a zinc-containing counter electrode, and has a simple structure. The electrochromic device of the present invention can reversibly switch between a colored state and a faded state under the action of an applied voltage, and can adjust the visible light transmittance. It can be used in building dimming windows, automotive dimming windows, and privacy dimming devices, showing promising application prospects. Attached Figure Description

[0020] Figure 1 This is a diagram illustrating the effects of polyiodide shuttle and dissolution in Comparative Example 1. Figure 1 a is a diagram illustrating the reaction mechanism of the electrochromic device in Comparative Example 1. Figure 1 b is an optical photograph of a simplified two-electrode electrolytic cell filled with the electrolyte of Comparative Example 1. Figure 1 c is the spectral absorption curve of the electrolyte in Comparative Example 1 after one coloring / bleaching cycle. Figure 1 d is the transmittance diagram of the electrochromic device of Comparative Example 1 after 100 cycles.

[0021] Figure 2 This is a diagram illustrating the effect of polyiodide shuttle and dissolution in the embodiment, wherein... Figure 2 a is an optical photograph of a simplified two-electrode electrolytic cell filled with the electrolyte of the embodiment. Figure 2 b is the spectral absorption curve of the electrolyte in the example after one coloring / bleaching cycle. Figure 2 c is the Raman spectrum of the black solid film deposited in the example. Figure 2 d is the in-situ Raman spectrum of the electrochromic device.

[0022] Figure 3 The structure of the electrochromic device prepared for the example is similar to that of I. - / I5 - Schematic diagram of the working principle of reversible inverter.

[0023] Figure 4 The image shows the working electrode of Comparative Example 2, which is a bare FTO electrode. Figure 4 a. Cyclic volt-ampere curve of the electrochromic device in Comparative Example 2 Figure 4 b is the transmittance diagram of the electrochromic device in Comparative Example 2 under different voltages. Figure 4 c shows the transmittance of the electrochromic device in Comparative Example 2 before and after 100 cycles.

[0024] Figure 5 This is a diagram illustrating the catalytic effect of RuO2 in the working electrode FTO / RuO2 of the example. Figure 5 a is a cyclic current-voltage (CV) curve of the electrochromic device in the embodiment. Figure 5 b is the linear sweep current-voltage (LSV) curve of the electrochromic device in Example 1 and Comparative Example 2. Figure 5 cd is the Tafel curve of the electrochromic device in the reduction and oxidation processes of the Example and Comparative Example 2.

[0025] Figure 6 The diagram shows the electrochemical performance of the electrochromic device in the embodiment. Figure 6 Image a shows the transmission and optical photographs of the electrochromic device in the bleaching and coloring states of the embodiment. Figure 6 b is a graph showing the coloring / fading response time of the electrochromic device in the embodiment at 650 nm. Figure 6 c shows the optical modulation rate of the electrochromic device in the embodiment after 20,000 coloring / fading cycles. Figure 6 d is a color rendering efficiency diagram of the electrochromic device in the embodiment. Detailed Implementation

[0026] To better understand the technical content of this invention, specific embodiments are provided below to further illustrate the invention.

[0027] Unless otherwise specified, the experimental methods used in the embodiments of this invention are all conventional methods.

[0028] Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available.

[0029] Preparation Example The preparation method of the FTO / RuO2 working electrode is as follows: FTO conductive glass is ultrasonically cleaned sequentially with anhydrous ethanol and deionized water for 15 min. After cleaning, the FTO conductive glass is treated with ultraviolet ozone for 10 min. The ultraviolet ozone treated FTO conductive glass is mounted on a rotating support, and RuO2 is deposited by DC reactive magnetron sputtering using a ruthenium metal target. The sputtering conditions are: sputtering atmosphere Ar flow rate 10 sccm, sputtering atmosphere O2 flow rate 8 sccm, sputtering pressure 3 Pa, sputtering power 45 W, deposition time 10 min, and the distance from the ruthenium metal target to the FTO conductive glass substrate is 10 cm, thus obtaining the FTO / RuO2 working electrode.

[0030] Example A type of I-based - / I5 - The fabrication method of reversible electrochromic devices includes the following specific steps: S1. Preparation of aqueous electrolyte Add 2.01 g of tetramethylammonium iodide, 13.63 g of ZnCl2 and 1.598 g of ZnI2 to 10 mL of water and stir well to obtain an aqueous electrolyte. S2. Assembly of electrochromic devices Using FTO / RuO2 as the working electrode and a zinc foil frame adhered to a glass substrate as the counter electrode, a 1mm spacer is provided between the working electrode and the counter electrode. An aqueous electrolyte is injected between the working electrode and the counter electrode, and the device is sealed with UV-curable adhesive to obtain an electrochromic device.

[0031] Comparative Example 1 The difference from the example is that tetramethylammonium iodide is not added to the aqueous electrolyte; otherwise, it is the same as the example.

[0032] Comparative Example 2 The difference from the embodiment is that the working electrode FTO / RuO2 is replaced with bare FTO, otherwise it is the same as the embodiment.

[0033] Test Example 1 Verification of N in the aqueous electrolyte of this invention 1111 + It can inhibit polyiodide shuttle; In non-metal electrodeposition type electrochromic devices, the composition and concentration of the electrolyte have a significant impact on the highly reversible redox of non-metal ions.

[0034] 1. See Figure 1 The reaction mechanism diagram of the electrochromic device in Comparative Example 1 shows that when an oxidation voltage is applied to the electrolyte of Comparative Example 1, iodide ions are oxidized on the surface of the working electrode to generate I3, which is soluble in the electrolyte. - I5 - Multiple iodides reduce the reversibility of the reaction.

[0035] Figure 1 b is an optical photograph of a simple two-electrode electrolytic cell filled with the electrolyte of Comparative Example 1. It can be seen that when the FTO / RuO2 working electrode and the zinc foil frame adhered to the glass substrate are inserted into the cuvette containing the electrolyte of Comparative Example 1, and a coloring voltage of 1.5V is applied for 10 s, a yellow colorant is rapidly generated on the surface of the FTO / RuO2 working electrode, and the electrolyte gradually turns yellowish-brown. Subsequently, after applying a bleaching voltage of 0.8V to the system for 20 s, the yellow colorant cannot completely disappear.

[0036] See Figure 1 The spectral absorption curve of the electrolyte in Comparative Example 1 (c) shows that after one coloring / fading cycle (1.5V (10 s) / 0.8V (20 s)), the electrolyte in Comparative Example 1 exhibits two distinct absorption peaks at 287 nm and 351 nm, corresponding to I3. - The characteristic absorption peak indicates a lack of N. 1111 + I3 generated at time - Polyiodides readily enter the electrolyte and cause severe shuttle.

[0037] from Figure 1 As can be seen from the transmittance diagram of Comparative Example 1 after 100 cycles, the optical modulation of the electrochromic device in Comparative Example 1 decreases significantly within 100 cycles.

[0038] 2. See Figure 2 An optical photograph of a simplified two-electrode electrolytic cell filled with the electrolyte of the embodiment shows that after applying a voltage of 1.5V for 10 seconds, a black solid film is formed on the surface of the FTO / RuO2 electrode, while the electrolyte remains transparent. Subsequently, after applying a voltage of 0.8V for 20 seconds, the black film disappears and the electrode returns to a transparent state.

[0039] See Figure 2 The spectral absorption curve of the electrolyte in Example b shows that no characteristic absorption peaks appeared in the electrolyte after one coloring / bleaching cycle.

[0040] Figure 2The Raman spectrum of the black solid film c shows that at 147 cm⁻¹... -1 With 156cm -1 The location belongs to I5 - The vibration peak.

[0041] from Figure 2 d of I - / I5 - The in-situ Raman spectrum of the electrochromic device shows that, when a coloring voltage of 1.5 V is applied, the Raman spectrum at 147 cm⁻¹... -1 156 cm -1 The peak at point I5 gradually increases, corresponding to I5. - The formation of these peaks, when a fading voltage of 0.8 V is applied, causes them to gradually disappear, indicating that I5... - Restored to I - This process is highly reversible.

[0042] 3. Working Principle See Figure 3 The electrochromic device prepared according to the embodiments of the present invention has a structure similar to that of I. - / I5 - A schematic diagram of the reversible inverter's working principle. In the fading state, iodine in the electrolyte mainly exists as I-. - The device exists in its original form and maintains high light transmittance. After applying a coloring voltage, RuO2 catalyzes I... - Oxidation occurs at the working electrode interface, forming I5. - N at the FTO / RuO2 electrode interface 1111 + It can rapidly react with the generated polyiodide ions I5 - A complex is formed, resulting in a black, opaque solid N. 1111 An I5 thin film is attached to the electrode surface. This film has high optical density, allowing the device to transition from a transparent state to a black or dark brown colored state, thus achieving coloring. When a reverse or lower fading voltage is applied, N... 1111 N in I5 complex 1111 + With I5 - The interaction between them is disrupted, N 1111 I5 gains an electron and is reduced to I. - Once the solid film disappears, the device becomes transparent again, completing the fading process.

[0043] The main reaction on the working electrode side is represented as follows: Coloring: N 1111 + + 5I - 4e - → N 1111 I5(s) Fading: N 1111 I5(s) + 4e - → N 1111 + + 5I - Therefore, compared with the soluble I3 of Comparative Example 1 - Compared to polyiodides, the solid N in the embodiments of the present invention... 1111 I5 can confine the coloring products to the surface of the working electrode, reducing shuttle and residual coloring caused by the diffusion of coloring species into the bulk electrolyte. The RuO2 catalyst layer reduces the polarization of the oxidation and reduction processes, enabling the device to complete coloring and fading rapidly at lower voltages.

[0044] Test Example 2 Verify the catalytic effect of RuO2 in the working electrode FTO / RuO2 of this invention; 1. See Figure 4 Comparative Example 2 shows the cyclic voltammetry (CV) curves of the electrochromic device. It can be seen that when using a bare FTO working electrode, I... - Complete oxidation requires a potential higher than 1.8 V, which is close to the oxygen evolution potential of aqueous electrolytes. This indicates that the device in Comparative Example 2 is highly susceptible to oxygen evolution side reactions during the coloring reaction, which can lead to device performance degradation.

[0045] from Figure 4 The transmittance of the electrochromic device in Comparative Example 2 at different voltages shows that when a coloring voltage of 1.8V is applied, the optical modulation amplitude of the electrochromic device in Comparative Example 2 in the visible light range of 400-800 nm is only about 20%, while at a coloring voltage of 2.0V, the optical modulation amplitude at 650 nm can reach 59.7%.

[0046] See Figure 4 c. The transmittance of the electrochromic device of Comparative Example 2 before and after 100 cycles. In the coloring / fading cycle test of the electrochromic device of Comparative Example 2 under 2.0 / 0.3 V conditions, its optical modulation rate decreased from 59.7% to 48.2% after only 100 cycles.

[0047] The above data indicates that I - / I5 - The high conversion barrier means that using a high coloring voltage will accelerate the degradation of device performance.

[0048] 2. In embodiments of the present invention, RuO2 is deposited on FTO conductive glass by magnetron sputtering as the working electrode of the electrochromic device. This is because the RuO2 surface is rich in active sites, and d-orbital electrons can form strong interactions with the reactants, promoting the breaking and formation of chemical bonds. See Figure 5 , Figure 5 a is a cyclic current-voltage (CV) curve of the electrochromic device in the embodiment. Figure 5 b is the linear sweep current-voltage (LSV) curve of the electrochromic device in Example 1 and Comparative Example 2. Figure 5 cd is the Tafel curve of the electrochromic device in the reduction and oxidation processes of the Example and Comparative Example 2.

[0049] from Figure 5 The LSV curve of b shows that at a current density of 0.1 mA•cm -2 In this embodiment, the overpotential of the electrochromic device is 1.17 V, which is 0.57 V lower than the 1.74 V of the electrochromic device in Comparative Example 2.

[0050] from Figure 5 The CV curve of example a shows that the electrochromic device in this embodiment exhibits an oxidation peak at 1.32 V and a reduction peak at 0.79 V. In contrast, the electrochromic device in Comparative Example 2 does not show a complete oxidation peak at 1.8 V, while the reduction peak appears at 0.53 V. It can be seen that when FTO / RuO2 is used as the working electrode in this embodiment of the invention, I... - / I5 - The oxidation potential of the transformation decreases significantly, while the reduction potential increases significantly. This is because RuO2 lowers the I... - / I5 - The reaction energy barrier of the conversion.

[0051] The Tafel slope is an important parameter characterizing electrode reaction kinetics; the smaller the value, the easier the reaction proceeds. Figure 5 c. Tafel plots of the electrochromic devices in the reduction process of Examples and Comparative Example 2, and Figure 5 From the Tafel curves of the electrochromic devices in the examples and Comparative Example 2 during the oxidation process, it can be seen that the electrochromic devices in the examples exhibit… - / I5 - During the transformation, the slopes of the Tafel slope under oxidizing and reducing conditions are 31 mV•dec. -1 and 72mV•dec -1 All were significantly lower than the electrochromic device of Comparative Example 2 (oxidation 353 mV•dec). -1 , reduce 183 mV•dec -1 This indicates that RuO2 has a catalytic effect and significantly promotes I - / I5 - Transformation.

[0052] Test Example 3 The electrochemical performance of the electrochromic device in the test embodiment was evaluated. 1. Optical transmittance: The transmission spectrum of the FTO / RuO2 electrode in the study embodiment was measured in the wavelength range of 400-800 nm, with air used as the baseline throughout the spectral testing.

[0053] See Figure 6 Transmission and optical photographs of the electrochromic device in bleached and colored states show that the electrochromic device of the embodiment has a visible transmittance of 77% in the transparent state, exhibiting high transmittance. When a coloring voltage of 1.5 V is applied, the electrochromic device rapidly changes from the transparent state to the black state within 5 seconds. After 10 seconds of coloring, the visible light transmittance further decreases to below 5%. At 650 nm, the optical modulation amplitude of the electrochromic device is as high as 75%, achieving a high opacity effect.

[0054] 2. Coloring / fading response performance: The in-situ dynamic spectrum of the FTO / RuO2 electrode in the electrolyte of the example was measured by applying a coloring voltage of 1.5V and a decolorizing voltage of 0.8V. See [link to example]. Figure 6 The coloring / fading response time diagram of the electrochromic device in embodiment b at 650 nm shows that, during the coloring and bleaching processes, the coloring response time of the electrochromic device in this embodiment is 3.9 s and the fading response time is 6.5 s, exhibiting fast ion transport kinetics (tc / tb = 3.9 s / 6.5), which is superior to the non-metallic deposition electrochromic devices of the prior art.

[0055] 3. Cyclic stability: A coloring voltage of 1.5V for 10s and a bleaching voltage of 0.8V for 20s were alternately applied to the FTO / RuO2 electrode, and N was measured. 1111 Cyclic stability of I5 deposition.

[0056] See Figure 6 The optical modulation rate diagram of the electrochromic device of embodiment c after 20,000 coloring / bleaching cycles shows that the optical modulation rate of the electrochromic device of embodiment c can still maintain the initial 84.9% after 20,000 cycles through repeated coloring and bleaching processes, indicating that the electrochromic device of embodiment c has good long-term reversibility and cycle stability.

[0057] 4. Coloring efficiency: Coloring efficiency (CE) refers to the change in optical density (ΔOD) per unit charge injection, and is an important performance indicator of electrochromic materials. It is calculated using the following formula:

[0058] In the formula OD and ΔQ represent optical density and charge density per unit area, respectively.

[0059] See Figure 6 The color rendering efficiency diagram of the electrochromic device in embodiment d shows that N of the present invention... 1111 The CE of the I5 thin film at 650 nm is 49.8 cm⁻¹. 2 / C, which is superior to existing non-metallic electrochromic technology, the ultra-high CE value of this invention indicates that the electrochromic device of this invention has large light modulation with small energy input, which is beneficial to energy saving.

[0060] The results from test examples 1-3 show that the tetramethylammonium cation forms solid N. 1111 I5 coloring film and RuO2 catalysis - / I5 - The synergistic effect enables the electrochromic devices prepared in the embodiments of the present invention to have high optical modulation, fast response, long cycle life and high coloring efficiency, and have good application prospects.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method based on I - / I5 - A method for fabricating a reversible electrochromic device, characterized in that, The specific preparation steps include: S1. Preparation of aqueous electrolyte Tetramethylammonium iodide, ZnCl2 and ZnI2 were added to water and stirred until homogeneous to obtain an aqueous electrolyte. S2. Assembly of electrochromic devices Using RuO2 / transparent conductive substrate as the working electrode and zinc-containing electrode as the counter electrode, the aqueous electrolyte is sandwiched between the working electrode and the counter electrode and sealed to obtain an electrochromic device.

2. A method based on I as described in claim 1 - / I5 - A method for fabricating a reversible electrochromic device, characterized in that, In step S1, the molar concentration of tetramethylammonium iodide in the aqueous electrolyte is 0.8-1.2 mol / kg, the molar concentration of ZnCl2 is 9-11 mol / kg, and the molar concentration of ZnI2 is 0.4-0.6 mol / kg.

3. A method based on I as described in claim 1 - / I5 - A method for fabricating a reversible electrochromic device, characterized in that, In step S2, the RuO2 / transparent conductive substrate electrode is prepared by depositing a RuO2 thin film on a transparent conductive substrate using DC reactive magnetron sputtering, with the sputtering atmosphere being a mixture of Ar and O2.

4. A method based on I as described in claim 3 - / I5 - A method for fabricating a reversible electrochromic device, characterized in that, The transparent conductive substrate is FTO conductive glass or ITO conductive glass.

5. A method based on I as described in claim 3 - / I5 - A method for fabricating a reversible electrochromic device, characterized in that, The specific preparation method of the RuO2 / transparent conductive substrate electrode is as follows: the transparent conductive substrate is ultrasonically cleaned sequentially with anhydrous ethanol and deionized water for 10-20 min; the cleaned transparent conductive substrate is then subjected to ultraviolet ozone treatment for 10-15 min; the ultraviolet ozone-treated transparent conductive substrate is mounted on a rotating support; and ruthenium metal target is used for DC reactive magnetron sputtering. The sputtering conditions are: sputtering atmosphere Ar flow rate 10-12 sccm, sputtering atmosphere O2 flow rate 7-8 sccm, sputtering pressure 3-4 Pa, sputtering power 40-45 W, deposition time 5-15 min, and the distance between the ruthenium metal target and the transparent conductive substrate is 10-12 cm.

6. A method based on I as described in claim 1 - / I5 - A method for fabricating a reversible electrochromic device, characterized in that, In step S2, the counter electrode is any one of a zinc foil frame, a zinc grid, or a zinc sheet attached to the surface of the glass substrate.

7. A method based on I as described in claim 1 - / I5 - A method for fabricating a reversible electrochromic device, characterized in that, In step S2, a spacer with a thickness of 0.5-2.0 mm is provided between the working electrode and the counter electrode, and it is sealed with UV-curable adhesive.

8. A method based on I - / I5 - A reversible electrochromic device, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

9. A method based on I as described in claim 8 - / I5 - A reversible electrochromic device, characterized in that, The electrochromic device includes a working electrode, a counter electrode, and an aqueous electrolyte. At a coloring voltage of 1.2-1.6V, I - I5 is formed by oxidation on the working electrode side. - I5 - The tetramethylammonium cation in the aqueous electrolyte forms a solid tetramethylammonium pentaiodide, which is deposited on the surface of the working electrode, coloring the device. Under a bleaching voltage of 0.7-0.9V, the solid tetramethylammonium pentaiodide is reduced to I... - It dissolves and causes the device to fade.

10. A method based on I as described in claim 8 - / I5 - Applications of reversible electrochromic devices in the fabrication of energy-efficient building windows, automotive dimming windows, or privacy dimming devices.